Agreement Between Courts and SVP Evaluators in the State of Wisconsin - Elwood, Richard W. (Criminal justice and behavior, 2019)
The study compares agreement between Department of Health Services (DHS) evaluator’s opinions and court decisions in all 132 sexually violent person (SVP) trials in Wisconsin from 2012 through 2016. Previous research on mock jurors in simulated SVP cases may not extend to real-world SVP legal proceedings. This is the first study to directly compare evaluator opinions with court decisions in actual SVP commitment cases. Trial courts found 81% of participants to be an SVP (SVP+). Courts agreed with the DHS evaluator’s opinion in 67% of the cases, which represents slight to fair agreement beyond chance. Trial courts agreed with evaluators’ SVP+ opinions far more than they did with evaluators’ SVP- (not SVP) opinions. The rates of SVP+ opinions differed widely among DHS evaluators. The implications for public policy and forensic practice are discussed.